India - "Bhandare, Namita(ed.)" (New Delhi, 2007)
The Hindustan Times Leadership Summit is an international forum for world leaders to share their vision for a future world. The annual summit is designed to create an environment for debate and discussion as key figures from across the globe present their dreams, concerns and aspirations to make the world a more harmonious place. At the conclusion of the fourth year of the summit, what was brought to the fore was more than just a blueprint for making India the next global superpower$1 (Bthe theme for the HT Leadership Summit 2006. Held in New Delhi in November, the speakers included Prime Minister Manmohan Singh; Indian National Congress President, Sonia Gandhi; President of Afghanistan, Hamid Karzai; Leader of UK's House of Commons, Jack Whitaker Straw; Commissioner, External Trade, European Union, Peter Mandelson; former New York Mayor Rudy Giuliani, former leader of UK's Labour Party Lord Neil Kinnock; and Chairman of the Communist Party of Nepal (Maoist), Prachanda, among others. Over two days of discussion, issues and roadblocks facing India's quest in becoming a world power were laid threadbare. This book is a result of that brainstorming.s
Keywords: Globalisation